2010 14th International Heat Transfer Conference, Volume 1 2010
DOI: 10.1115/ihtc14-22664
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of External Electric Field on Heat Transfer at Boiling on Non-Uniform Surfaces

Abstract: Characteristics of heat transfer and hydrodynamics of boiling of liquid nitrogen on the surfaces with different types of non-uniformities at the presence of external electric fields are experimentally investigated. It is shown that the formation of field traps is a major mechanism of heat transfer enhancement. And this effect result in noticeable change of two-phase hydrodynamics in vicinity of heated surface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Recently, some attention has been given to the study on electric field effects on pool boiling from heated surfaces with microstructures and roughness [10][11][12]. For example, Borzenko et al [10] used a mesh electrode to study the ''field trap effect'' on a heating surface with a single rib.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, some attention has been given to the study on electric field effects on pool boiling from heated surfaces with microstructures and roughness [10][11][12]. For example, Borzenko et al [10] used a mesh electrode to study the ''field trap effect'' on a heating surface with a single rib.…”
Section: Introductionmentioning
confidence: 99%
“…They found that due to the field trap effect in the presence of an electric field, vapor bubbles escaping under the rib have a larger departure diameter and a lower departure rate than those in the absence of an electric field. Eronin et al [11,12] carried out boiling experiments of liquid nitrogen on a heated surface with a rectangular rib. They pointed out that a non-uniform electric field forms in the dielectric liquid, and the dielectrophoretic force pushed the bubbles between the ribs to the bottom of ribs first, and subsequently, pushed the vapor bubbles out of the regions of the vertices of ribs.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, some methods, including twisted wire, twisted strip, or other tools, which provide fluid flow rotation, are classified in this category . For example, use of harsh surfaces, extended surfaces, twisted pipes, and fluid additives does not require direct external power while active techniques, such as mechanical, surface vibration, liquid vibration, electrostatic fields, and suction/injection, require a power supply. San and Huang studied the increase of heat transfer transverse gears in circular tubes taking into account the input effect.…”
Section: Introductionmentioning
confidence: 99%